Essential oils in the control of dry bubble disease in white button mushroom - Santos,Tamara Leite dos (2017)
ABSTRACT: Lecanicillium fungicola, which causes Dry bubble disease, induces infections and inflicts major losses in champignon production. The control can be managed through measures of hygiene and use of fungicides; however, in Brazil there are no registered products. This study aimed to estimate the influence of various essential oils extracted from Melissa officinalis, Thymus vulgaris, Origanum vulgare, Eucalyptus globulus, Cinnamomum zeylanicum and Syzygium aromaticum on the in vitro development and their uses. Therefore, analysis was performed of the L. fungicola isolates in vitro and the best oils were tested in vivo. Besides, the Agaricus bisporus - L. fungicola interaction was confirmed by scanning electron microscopy (SEM). Cinnamon and clove oils in concentrations of 0.4% and thyme oil of 0.8% were identified as good growth inhibitors of the pathogenic mycelium. Effective inhibition of the conidial germination was seen in all concentrations by cinnamon oil, and by clove and thyme oils only at 0.4% and 0.8%, respectively. When the essential oils were applied post-infestation in the in vivo experiments the incidence of the disease in the mushrooms was much lower. From the SEM it was clear that 19 hours after the inoculation of A. bisporus with L. fungicola, the spores had already completely germinated, revealing the presence of the infection. Therefore, the findings of this study indicated that the oil extracts of cinnamon, clove and thyme are potential and efficient alternatives in the control of dry bubble disease.